Strategic planning of hotel sector development in Ukraine - Semikolenova, S. (Культура народов Причерноморья, 2004)
Tourist industry in Ukraine and its' hotel sector is still in its developing stage. The "Law on Tourism" was adopted only in autumn of 2003. It is very important to understand what forces are behind the development of hospitality industry since it affects the development of construction, service and communication sectors and thus has a potential of increasing GDP and government revenues.